CLINICO-DEMOGRAPHIC STUDY OF PATIENTS WITH ACANTHOSIS NIGRICANS - A MENACE FOR CARDIO-VASCULAR DISEASE - Das, Suchibrata; SETT, ARINDAM; SAHA, ABANTI; Patra, Sangita; Gharami, Ramesh CH. (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Acanthosis nigricans (AN) is characterized by dark, coarse, and thickened skin with a velvety texture, involving the neck, the axillae, and the flexor of large joints. A significant association between coronary heart disease and patients with AN was noticed. Objectives were to study the prevalence, clinico-demographic, and etiological profile of patients presenting with AN and to draw relations, if any, with cardiovascular disease (CVD). Methods: It was an observational, descriptive, institution-based cross-sectional study and was conducted at the out-patient department of dermatology, venereology and leprosy of a tertiary care hospital in the eastern part of India. An attempt was made to detect the etiological factor of the disease by noting the temporal association between the disease and any systemic associations, with special attention to CVD. Results: High body mass index (BMI) was seen in 71.9% of cases, systolic hypertension in 35.3%, diastolic hypertension in 43.9%, raised fasting blood sugar (FBS) in 30.2%, and raised postprandial (PP) sugar in 15.8% of patients. A significant relationship was seen between high BMI, raised cholesterol, triglycerides, and PP blood sugar and systolic and diastolic hypertension. Conclusion: In AN, patients who have a high BMI have the highest chance of developing CVD, as well as hypercholesterolemia and hypertryglyceridemia. Raised FBS is noted as an additional factor for developing diastolic hypertension.